Uso de microarrays na busca de perfis de expressão gênica: aplicação no estudo de fenótipos complexos - Guindalini, Camila [UNIFESP] (2007)
Sequencing the human genome has prompted the development of new technologies, which have emerged as promising methodological and scientific tools for advancing the current knowledge about the causes and mechanisms involved in various complex disorders. Among those, the high-throughput technique known as microarray is particularly powerful in providing a global view of gene expression patterns in biological samples. By the simultaneous determination of the expression levels of thousands of genes, microarrays allow researchers to compare the molecular behaviour of different types of cells lines or specific tissues that have been exposed to pathological or experimental conditions. The method may provide insights into physiological processes and facilitate the identification of novel biological markers for diagnostic, prognostic and pharmacological treatments for a number of diseases. In this article, we present theoretical and methodological concepts underlying the microarray technology, as well as an overview of its advantages, perspectives and future scientific directions. In an attempt to demonstrate the applicability and efficiency of the method in the study of complex phenotypes, initial results on gene expression studies in post mortem brain samples of psychiatric patients and on the molecular and functional consequences of sleep disturbances, which is strongly associated with psychiatric illness, will be described and discussed.